Using faculty focus groups to launch a scholarly communication program - Courtois, Martin P.; Turtle, Elizabeth C. (My University, 2008)
This paper explores the benefits of using faculty focus groups as an early component of a scholarly communications program with suggestions for planning and conducting sessions, recruiting participants and analyzing outcomes.
Keywords: Focus groups; Scholarly communications; Faculty